Synthesis of novel 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones derivatives - A. A. Safonov; A. V. Nevmyvaka (Zaporozhye State Medical University, 2020)
A wide range of biological activity of 1,2,4-triazole derivatives (anti-inflammatory, antiviral, antitumor, immunostimulating, etc.) and the availability of sources for their preparation determine the prospects of using compounds of this class to create modified derivatives based on them and, as a result, medicines. Derivatives of 1,2,4-triazole have already established themselves both in the agricultural sector and in veterinary medicine and pharmacy. The aim of work was to synthesize 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones, 2-((5-(2-bromophenyl)-4-methyl-4H-1,2,4-triazole-3-yl)thio)acetic acids and their salts. Materials and methods. 3-(2-Bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones (4a-4c) were synthesized by refluxing 1 mol 2-(2-bromobenzoyl)-N-substitutedhydrazinecarbothioamides (3a-3c) with 2 mol KOH in water medium and after cooling neutralized with acetic acid. 2-((5-(2-Bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetic acids (5a-5c) were obtained by refluxing the solution of 0,1 mol NaOH and substances 4a-4c respectively. It was dissolved in 2-propanol medium with 0,1 mol 2-chloroacetic acid. 2-((5-(2-Bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetic acid salts (6a-6o) were synthesized by adding organic amines or inorganic salts to substances 5a-5c respectively in 2-propanol or water medium. The elemental analysis of synthesized compounds was established by the universal analyzer Elementar Vario L cube (CHNS). The 1H spectra (at 400 MHz and 100 MHz) were recorded in DMSO-d6 on a Varian MR-400 spectrometer and analyzed with the ADVASP™ Analyzer program. The completeness of the reactions and the individuality of the resulting compounds were controlled by the gas chromatograph Agilent 7890B with a 5977B mass spectrometry detector. Results. It was synthesized new 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thionesand there derivatives, the structure of compounds was confirmed using Elemental analysis (CHNS), 1HNMR and Chromatographic mass spectral analysis. Conclusions. As a result, 21 novel compounds of 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones were synthesized and characterized.